An Empirical Analysis of the Taylor Rule and Its Application to Monetary Policy: A Case for the United Kingdom and Euro Area - Bhattarai, Keshab; Carter, Matthew (Asian Journal of Economics and Empirical Research, 2018)
This paper analyses the Taylor rule and its application to monetary policy in the United Kingdom and Euro area. The analysis uses a linear regression on quarterly economic data from 1993Q1 to 2017Q4 for the United Kingdom and 2000Q1 to 2016Q4 for the Euro area. The results show that the Taylor rule does not fully describe the monetary policy actions made by the Bank of England and European Central Bank over the period analysed; and, that both central banks engage in a significant level of interest rate smoothing. The results also suggest that the Taylor rule does not provide the rationale for quantitative easing within the two regions and that interest rates should be higher than they currently are.